2006
DOI: 10.1523/jneurosci.2379-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Independent Regulation of Dendrite Patterning by Postsynaptic Density Protein PSD-95

Abstract: Dendritic morphology determines many aspects of neuronal function, including action potential propagation and information processing. However, the question remains as to how distinct neuronal dendrite branching patterns are established. Here, we report that postsynaptic density-95 (PSD-95), a protein involved in dendritic spine maturation and clustering of synaptic signaling proteins, plays a novel role in regulating dendrite outgrowth and branching, independent of its synaptic functions. In immature neurons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
161
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 55 publications
9
161
1
2
Order By: Relevance
“…Previous studies have shown that PSD-95 contributes to the processes of dendrite development, spine formation, and spine maturation (38). Furthermore, the involvement of PSD-95 in dendritic spine maturation and clustering of synaptic signaling proteins indicates the critical role this protein has in regulating dendritic outgrowth and branching (39). Although the precise impact of irradiation on these processes is relatively unknown, past work has shown that in immature neurons, overexpression of PSD-95 decreases the proportion of primary dendrites that undergo additional branching, resulting in marked reductions of secondary dendrites (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PSD-95 contributes to the processes of dendrite development, spine formation, and spine maturation (38). Furthermore, the involvement of PSD-95 in dendritic spine maturation and clustering of synaptic signaling proteins indicates the critical role this protein has in regulating dendritic outgrowth and branching (39). Although the precise impact of irradiation on these processes is relatively unknown, past work has shown that in immature neurons, overexpression of PSD-95 decreases the proportion of primary dendrites that undergo additional branching, resulting in marked reductions of secondary dendrites (39).…”
Section: Discussionmentioning
confidence: 99%
“…), neurons were transfected using the Effectene reagent (QIAGEN, Valencia, CA) as is done routinely in our laboratory. 3,4,15 Cultures were allowed to express the transfected proteins for 48 h. Images of transfected hippocampal neurons were taken as described previously, 4 and neurons were confirmed by MAP2 immunostaining. Primary and secondary dendrites were counted as previously described.…”
Section: Neuronal Culture Transfection and Dendrite Branching Numbementioning
confidence: 99%
“…Primary and secondary dendrites were counted as previously described. 3,4,15 To acquire unbiased dendrite number counts, the analyzing person was blinded to the transfection condition.…”
Section: Neuronal Culture Transfection and Dendrite Branching Numbementioning
confidence: 99%
“…We previously reported that PSD-95 decreases dendrite branching by disrupting microtubule organization (Charych et al, 2006;Sweet et al, 2011a,b). Moreover, PSD-95 is in a complex with F-actin, and PSD-95 overexpression enhances dendritic spine formation and stabilization (Okabe et al, 1999;El-Husseini et al, 2000;Horne and Dell'Acqua, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, PSD-95 is in a complex with F-actin, and PSD-95 overexpression enhances dendritic spine formation and stabilization (Okabe et al, 1999;El-Husseini et al, 2000;Horne and Dell'Acqua, 2007). Cypin increases dendrite branching by promoting microtubule polymerization and negatively regulating PSD-95 clustering (Firestein et al, 1999;Akum et al, 2004;Charych et al, 2006). Accordingly, cypin and PSD-95 may be involved in the machinery that maintains dendrite integrity and promotes spine retraction and reemergence in response to sublethal glutamate exposure.…”
Section: Introductionmentioning
confidence: 99%